The influence of the principal’s leadership to teacher performance - Sulastri, Tuti; Hendriana, Tengku Ine; Ratnaningsih, Rini; Nur Fadhilah, Rizki (Junal Ilmu Manajemen, 2024)
The principal's leadership is one of the determining factors for improving teacher performance in schools because it is very important to determine the high and low learning outcomes of students, productivity and morale of teachers. This can determine the extent to which the principal is able to create work excitement and encourage his subordinates to work in accordance with the policies and programs that have been outlined, so that discipline, work productivity, high teacher performance and student learning outcomes increase. This study was conducted to determine the influence of the principal's leadership on teacher performance. This study used quantitative research methods with questionnaire data collection techniques. The population in this study is all teachers with a total of 12 people, because the population does not eat much using the saturated sample technique (census) where the entire population is used as a sample. This study shows the results that: The principal's leadership has a significant effect on teacher performance, because the calculation results show the value of t (1) count is 17.338 while t table shows a number of 2.201, thus t calculate the > t table and the specified significance level (α) = 5% with sign. < 0.05 is 0.00, then H0 is rejected, Hi is accepted. The hypothesis indicates that Leadership (X) has a significant effect on Performance (Y). Extent the principal is able to create work excitement and to what extent the principal is able to encourage his subordinates to work in accordance with the policies and programs that have been outlined so that discipline, work productivity and teacher performance are high and student learning outcomes are improved.